The cryo‐EM structure of full‐length RAD52 protein contains an undecameric ring - Chiaki Kinoshita; Yoshimasa Takizawa; Mika Saotome; Shun Ogino; Hitoshi Kurumizaka; Wataru Kagawa (FEBS Open Bio, 2023)
The human RAD52 protein, which forms an oligomeric ring structure, is involved in DNA double‐strand break repair. The N‐terminal half of RAD52 is primarily responsible for self‐oligomerisation and DNA binding. Crystallographic studies have revealed the detailed structure of the N‐terminal half. However, only low‐resolution structures have been reported for the full‐length protein, and thus the structural role of the C‐terminal half in self‐oligomerisation has remained elusive. In this study, we determined the solution structure of the human RAD52 protein by cryo‐electron microscopy (cryo‐EM), at an average resolution of 3.5 Å. The structure revealed an undecameric ring that is nearly identical to the crystal structures of the N‐terminal half. The cryo‐EM map for the C‐terminal half was poorly defined, indicating that the region is intrinsically disordered. The present cryo‐EM structure provides important insights into the mechanistic roles played by the N‐terminal and C‐terminal halves of RAD52 during DNA double‐strand break repair.